Animals without backbones: viva education: science works for kids series - Moore, Jo Ellen (Viva Education New Delhi, 2004)
This informative book introduces young readers to invertebrates, showcasing a variety of animals that lack a backbone, such as insects, jellyfish, and worms. Through colorful illustrations and engaging text, it highlights their unique features, habitats, and roles in the ecosystem, encouraging curiosity about the diverse world